Strategi Bersaing Konter Pulsa Konvensional di Era E-Commerce - Akmal Auliya Amri; Vera Pujani; Yulia Hendri Yeni (Jurnal Informatika Ekonomi Bisnis, 2023)
This research was conducted to find out the business processes, influencing factors and strategies used by celluler kiosk in the city of Padang. This study uses a descriptive qualitative approach. The data in this study were obtained from primary data in the form of interviews with respondents. In this study, interviews were conducted with 11 respondents who were celluler kiosk business actors in the city of Padang. The results of the study show that the this business is still promising amidst the development of e-commerce. 8 out of 11 informants said that e-commerce has not had an effect on business. 10 informants have not used online channels in making sales. To compete and survive, this business needs to develop a competitive strategy. This is done by providing inexpensive services and products (cost leadership), unique and diverse products (differentiation) or opening online channels on social media or e-commerce.